2009
DOI: 10.1093/neuonc/nop026
|View full text |Cite
|
Sign up to set email alerts
|

Akt2 and Akt3 play a pivotal role in malignant gliomas

Abstract: Akt, one of the major downstream effectors of phosphatidylinositol 3-kinase, is hyper-expressed and activated in a variety of cancers including glioblastoma. However, the expression profiles of the Akt isoforms Akt1/PKBa, Akt2/PKBb, and Akt3/PKBg and their functional roles in malignant glioma are not well understood. Therefore, we examined the protein and mRNA expression patterns of Akt isoforms in tissues from human astrocytomas, glioblastomas, and non-neoplastic regions. We also explored the biological role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 36 publications
9
88
2
Order By: Relevance
“…Akt3 is expressed at lower levels in vascular tumors than in normal blood vessels. Such a scenario has also been observed in malignant glioma, in which the expression of Akt3 is lower in the tumor than in normal brain tissue; however, the remaining Akt3 has kinase activity (36). This suggests that although the level of endogenous Akt3 is reduced, it still retains the functional capacity as an active kinase.…”
Section: Discussionmentioning
confidence: 70%
“…Akt3 is expressed at lower levels in vascular tumors than in normal blood vessels. Such a scenario has also been observed in malignant glioma, in which the expression of Akt3 is lower in the tumor than in normal brain tissue; however, the remaining Akt3 has kinase activity (36). This suggests that although the level of endogenous Akt3 is reduced, it still retains the functional capacity as an active kinase.…”
Section: Discussionmentioning
confidence: 70%
“…Mice lacking Akt1 have small body size, mice lacking Akt2 show a diabetic phenotype, and mice lacking Akt3 have reduced brain size (Cho et al 2001a,b, Easton et al 2005, Tschopp et al 2005. In melanoma cells, Akt3 was found to be the principal Akt isoform involved in tumor development, while in malignant glioma, Akt2 was shown to promote cell migration, invasion, and viability (Stahl et al 2004, Zhang et al 2009, Mure et al 2010. In breast cancer, Akt1, though playing an important role in tumor induction, inhibits metastasis while Akt2 exhibits promigratory effects and facilitates proliferation and cell survival (Hutchinson et al 2004, Dillon et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The first studies were reported on Akt2 only, which was found to mediate invasion in rat C6 glioma cells (13), and inhibition of Akt2 prolonged survival in an orthotopic rat model (14). Subsequent reports have found that Akt2, and possibly Akt3, are important for disease progression and maintenance, whereas Akt1 does not play a major role (15,16). Another study in transformed mouse astrocytes indicate that Akt isoform function is potentially modulated by the genetic landscape of the tumor (17).…”
mentioning
confidence: 99%